New photodynamic molecular beacons (PMB) as potential cancer-targeted agents in PDT. Issue 3 (1st February 2018) - Stallivieri, Aurélie; Colombeau, Ludovic; Devy, Jérôme; Etique, Nicolas; Chaintreuil, Carine; Myrzakhmetov, Bauyrzhan; Achard, Mathilde; Baros, Francis; Arnoux, Philippe; Vanderesse, Régis; Frochot, Céline
Graphical abstract: Abstract: Further improvements in Photodynamic therapy (PDT) necessitate that the dye targets more selectively tumour tissues or neovascularization than healthy cells. Different enzymes such as matrix metalloproteinases (MMPs) are overexpressed in tumour areas. Among these MMPs, gelatinases (MMP-2 and MMP-9) and its activator MMP-14 are known to play a key role in tumour angiogenesis and the growth of many cancers such as glioblastoma multiforme (GBM), an aggressive malignant tumour of the brain. These last years, the concept of photodynamic molecular beacons (PMB) became interesting for controlling the photosensitizer's ability to generate singlet oxygen ( 1 O2 ) close to target biomolecules as MMPs. We report herein novel PMBs triggered by MMP-2 and/or MMP-9 and/or MMP-14, comprising a photosensitizer and a singlet oxygen quencher linked by MMP cleavable peptide linker (H-GRIGFLRTAKGG-OH). First of all, we focused on the synthesis and the photophysical study of different derivatives photosensitizer-peptide. This preliminary work concluded on an influence of the nature and the distance from the peptide, but not of the position of the photosensitizer in these derivatives on the proteolytic enzymatic action. The nature of the quencher used (a blackberry quencher (BBQ-650) or a black hole quencher (BHQ3)) does not influence the enzymatic action. We also studied the influence of an additional PEG spacer. Finally, the synthesis, the singlet oxygen quenching efficiency and the enzymatic activation of these new MMP- cleavable-PMBs were compared.